Bio-electrochemical system (BES) as an innovative approach for sustainable waste management in petroleum industry. (October 2018) - Srikanth, Sandipam; Kumar, Manoj; Puri, S.K.
Graphical abstract: Highlights: Diverse range of waste/wastewater produced from petroleum industry are deliberated. BES role in sustainable waste management coupled to meeting the growing energy demand discussed. Possible options for valorisation waste in different forms of BES discussed. Major challenges of BES application in petroleum industry detailed. Abstract: Petroleum industry is one of the largest and fast growing industries due to the ever increasing global energy demands. Petroleum refinery produces huge quantities of wastes like oily sludge, wastewater, volatile organic compounds, waste catalyst, heavy metals, etc., because of its high capacity and continuous operation of many units. Major challenge to this industry is to manage the huge quantities of waste generated from different processes due to the complexity of waste as well as changing stringent environmental regulations. To decrease the energy loss for treatment and also to conserve the energy stored in the chemical bonds of these waste organics, bio-electrochemical system (BES) may be an efficient tool that reduce the economics of waste disposal by transforming the waste into energy pool. The present review discusses about the feasibility of using BES as a potential option for harnessing energy from different waste generated from petroleum refineries.